Substance Use Disorder Typologies of Canadian Federally Sentenced Men: Relationships With Institutional Behavior and Postrelease Success - Ternes, Marguerite (Criminal justice and behavior, 2019)
This study explored the presence of subgroups of incarcerated offenders using cluster analysis. Subgroups were created based on severity of criminogenic needs, including substance use, from a retrospective cohort of 5,275 Canadian male incarcerated offenders. Five groups emerged: (a) Primarily Drug Users With Stable Employment/Education, (b) Primarily Drug Users with High Needs, (c) Polysubstance Users With Positive Social Supports, (d) Polysubstance Users With Severe Need for Intervention, and (e) Drug Offenders With Good Reintegration Potential. Sociodemographic factors, criminal history, institutional behavior, and rates of recidivism were explored across subgroups. Drug Offenders With Good Reintegration Potential had the lowest rates of institutional charges and recidivism, while offenders in the Primarily Drug With High Needs and Polysubstance With Severe Need for Intervention groups had the highest rates. These findings highlight that classification of offenders is complex and nuanced. Knowing the pattern and severity of substance use and criminogenic needs aids offender management.